Fully realized humans [videorecording (DVD)] - Leonard, Joshua; Leonard, Joshua; Weixler, Jess; Weixler, Jess; Chieffo, Michael; Grant, Beth, 1949-; Bower, Tom, 1938- (Gravitas Ventures, 2021)
With less than a month until the birth of their first child, Jackie and Elliot embark on a madcap mission of self-discovery in an attempt to rid themselves of the inherited baggage of their own childhoods. Fully Realized Humans or bust!